2019
DOI: 10.5380/revsbau.v7i1.66550
|View full text |Cite
|
Sign up to set email alerts
|

Composição Florística Da Arborização Da Cidade De Altamira, Pará.

Abstract: Foi realizado em 2010, um inventário da arborização da cidade de Altamira, Pará. Foram amostradas todas as vias públicas dos 25 bairros, com a utilização de uma planilha estruturada para a realização do censo total das espécies presentes nas vias. Foram identificadas 4.294 plantas de 120 espécies, de 105 gêneros e distribuídas em 40 famílias botânicas. A espécie mais frequente foi o ficus (Ficus benjamina), com um total de 1.062 espécimes que representaram 24,7% das árvores da cidade. A segunda espécie mais fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Studies about urban forestry in the Brazilian Amazonia have shown that people have been primarily responsible for planting and cultivating plant species located on the streets [28,33]. In this sense, the municipal government needs to prioritize the planning of actions related to urban forestry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies about urban forestry in the Brazilian Amazonia have shown that people have been primarily responsible for planting and cultivating plant species located on the streets [28,33]. In this sense, the municipal government needs to prioritize the planning of actions related to urban forestry.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of urban forestry, we mention that an inventory of the afforestation of the city of Altamira (PA) was carried out, through a partnership between the City Hall, higher education institutions, and the Public Ministry [28]. The results showed a great presence of exotic species, and for that reason, actions of production of seedlings of native species have been carried out for cultivation in the urban forestry of this city, such as Handroanthus serratifolius, Andira parviflora, and Clitoria racemosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O crescimento urbano acelerado e desordenado de uma cidade acarreta a criação de novos bairros sem planejamento adequado, ocasionando o surgimento de muitos conflitos urbanos, dentre eles, os problemas com o componente vegetal urbano (PARRY et al, 2012). A vegetação urbana desempenha funções essenciais e diversas nos centros urbanos, dentre as quais podemos citar a influência no conforto térmico do ambiente urbano através da produção de sombra, amenizando a temperatura, o aumento do teor de oxigênio e de umidade, a absorção de gás carbônico, além de influenciar na qualidade do ar atuando como filtro de poluentes, operar como barreiras acústicas, melhorar as condições do solo e caracterizar a beleza natural dos ambientes urbanos (MELO et al, 2007).…”
Section: Introductionunclassified